The Familiar and Unknown - Wills, Janelle (Auckland University of Technology, 2013)
This practice‐based project is an exploration of how sensations of ‘the Uncanny’ can be evoked through pictorial form. This has involved an in-depth investigation into the signification of the subject matter I employ, along with its means of description via an examination of the conceptual and applied characteristics of photography and the medium of paint. Through the transaction between photographic reality (as documented through the ‘objective’ camera lens) and the visceral effects of painted expression, I disrupt what is familiar with what is unknown. I create work which activates an atmosphere where something has happened, will happen or is happening quietly and unseen, an atmosphere implied by a residual mood or echo that resonates from what is missing. Through sensitively cropped representations of landscape and suburban scenes my work activates a concept of absence via signs of human activity. The mundane subject matter of my paintings - clotheslines, rubbish bins, backyards - abandoned by their occupants, appear populated instead by emptiness, stillness and silence. I am interested in drawing the viewer in through the everyday and the known, whilst simultaneously employing the same banal imagery to create a sinister undertone that interrupt certainty and comfort, and alludes to something more ominous.
Keywords: Das unheimlech; The uncanny